Aptamers in HIV research diagnosis and therapy. Issue 3 (4th March 2018) - Bala, Jyoti; Chinnapaiyan, Srinivasan; Dutta, Rajib Kumar; Unwalla, Hoshang
ABSTRACT: Aptamers are high affinity single-stranded nucleic acid or protein ligands which exhibit specificity and avidity comparable to, or exceeding that of antibodies and can be generated against most targets. The functionality of aptamers is based on their unique tertiary structure, complexity and their ability to attain unique binding pockets by folding. Aptamers are selected in vitro by a process called Systematic Evolution of Ligands by Exponential enrichment (SELEX). The Kd values for the selected aptamer are often in the picomolar to low nanomolar range. Stable and nontoxic aptamers could be selected for a wide range of ligands including small molecules to large proteins. Aptamers have shown tremendous potential and have found multipurpose application in the field of therapeutic, diagnostic, biosensor and bio-imaging. While their mechanism of action can be similar to that of monoclonal antibodies, aptamers provide additional advantages in terms of production cost, simpler regulatory approval and lower immunogenicity as they are synthesized chemically. Human immunodeficiency virus (HIV) is the primary cause of acquired immune deficiency syndrome (AIDS), which causes significant morbidity and mortality with a significant consequent decrease in the quality of patient's lives. While cART has led to good viral control, people living with HIV now suffer from non-HIV comorbidities due to viral protein expression that cannot be controlled by cART. Hence pathophysiological mechanisms that govern these comorbidities with a focus on therapies that neutralize these HIV effects gained increased attention. Recent advances in HIV/AIDS research have identified several molecular targets and for the development of therapeutic and diagnostic using aptamers against HIV/AIDS. This review presents recent advances in aptamers technology for potential application in HIV diagnostics and therapeutics towards improving the quality of life of people living with HIV.